Analysis of mushroom supply: Determinants and elasticity factors - Fahlevi, Andrew; Rahayu, Endang Siti; Antriyandarti, Ernoiz (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: This study aims to determine the factors that influence the supply and elasticity of mushroom supply in Malang. Method: The primary method used in this research is descriptive and analytic. The research location was chosen purposively in Malang. The type of data used is secondary data in the form of time series for 39 months. The data analysis method used is multiple regression linear analysis with the partially adjusted Nerlove Model. Findings: The results showed the variable price of mushrooms, the area of the harvested mushroom, the price of chicken meat, the price of urea fertilizer, and interest rates individually affected the supply of mushrooms in Malang. The variable of mushroom production and the average rainfall had no significant effect. Variables that are elastic in the short term are the area of the harvested mushroom, and elastic in the long term are the area of the harvested mushroom and the price of chicken meat. Conclusion: The mushroom farmer needs production planning to anticipate increases in the price of substitution products. Mushroom farmers are advised to make storage for supply and expand the mushroom house with more substantial materials to increase supply. Novelty/Originality of this study: This analysis provides an in-depth understanding of supply dynamics, identifying key factors that influence supply elasticity in the short and long term. This study offers practical recommendations for mushroom farmers to optimize their production in the face of market fluctuations.